Analysis of carbon emissions embodied in South Korea's international trade: Production-based and consumption-based perspectives. (20th October 2021) - Kim, Tae-Jin; Tromp, Nikolas
Abstract: Growing international trade is likely to become a major obstacle in reducing carbon emissions. Research that estimates trade-related emissions and analyzes the sources will be important to overcoming this obstacle. With this in mind, the current paper investigates carbon emissions embodied in South Korea's trade during 2000–2014. Using multi-regional input-output analysis, we find large increases in emissions embodied in exports (production-based emissions) and imports (consumption-based emissions) which drove increases in Korean emissions. Over time, Korea's net carbon exports grew alongside its net value-added exports, implying a greater trade-off between the environmental costs and economic benefits of trade. However, emission intensities of exports and imports both fell which suggests improvements in emission efficiencies at home and abroad. Analysis of bilateral trade shows that growth in trade with China accounted for the largest share of increases in Korea's embodied emissions. Analysis at the sectoral level shows high levels of emissions relative to value added in basic materials and transportation services but low levels of emissions relative to value added in electronic and mechanical equipment and transportation equipment. Lastly, structural decomposition analysis indicates that improvements in emission intensities limited growth in emissions, while rising levels of final demand expanded growth in emissions. As the first extensive study to analyze the drivers of changes in Korea's carbon emissions embodied in multilateral exports and imports, this paper recommends various abatement policies to effectively reduce emissions. Graphical abstract: Image 1 Highlights: CO2 emissions embodied in Korea's trade during 2000–2014 were estimated. Production-based and consumption-based CO2 emissions were measured. Multi-regional input-output and structural decomposition methods were applied. Korea's net CO2 emissions exports increased considerably during 2007–2014. The scale of final demand contributed most to the rise in Korea's emissions.